Using Altman Z-Score Model and Current Status Of Financial Ratio to Asses Of Consumer Goods Company Listed in Indonesia Stock Exchange (IDX) - Yoppy Palupi Purbaningsih (UBL, 2013)
This study aims to assess the financial condition of the companies listed on the Indonesia Stock Exchange (IDX) using a model of financial distress prediction Edward Altman Z-score and the Current Ratio. The population in this study consisted of 33 Consumer Goods Company at the period 2009-2010 in Indonesia Stock Exchange (IDX). The data used is secondary data obtained from the companys financial statements. Testing hypotheses using paired sample t test..Results of this study found that There is a significant difference between the use of Altman Z-score and Current Ratio method in determining the financial condition of Consumer Goods Companies listed in Indonesia Stock Exchange (IDX). In addition there is the Financial Distress in Consumer Goods Company listed on the Indonesia Stock Exchange (IDX). From the results of this study can be concluded that Altman Z-Score model and the current ratio is a useful tool for investors to predict the companys financial failure.